2017
DOI: 10.18203/2394-6040.ijcmph20173817
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of biomedical waste management of a multispeciality hospital in the light of new BMW rules 2016: what has changed from the past?

Abstract: Background: The hierarchies of Bio-Medical Waste (BMW) is largely based on the concept of the “3Rs”, namely reduces, reuse and recycle, and broadly relates to the sustainable practice of resources. The objectives of the study were to assess the Bio-Medical Waste (BMW) Management operating system in a multispecialty hospital and discuss the situation in terms of newly introduced BMW Rules 2016.Methods: A hospital based cross-sectional study was carried out by collecting data by means of independent surveys invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
(5 reference statements)
2
2
0
Order By: Relevance
“…Biomedical wastes such as sharps are treated and disposed of by incineration and landfills. This agrees with a previous study [21] where incineration, autoclaving, and shredding of sharps were employed. Incineration was the major means of treatment, and autoclaving was employed for the treatment of a few medical wastes [1], and infectious wastes and sharps were incinerated [28].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Biomedical wastes such as sharps are treated and disposed of by incineration and landfills. This agrees with a previous study [21] where incineration, autoclaving, and shredding of sharps were employed. Incineration was the major means of treatment, and autoclaving was employed for the treatment of a few medical wastes [1], and infectious wastes and sharps were incinerated [28].…”
Section: Resultssupporting
confidence: 93%
“…The result showed that the respondents practiced disinfection, microwaving, and shredding. This agrees with an earlier study [21]. The result showed that respondents supported the practice of chemical disinfection of infectious wastes generated from the laboratories and theatres.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…3 Considerable amount of BMW is being generated from the health and related sector, be it the medical and dental hospitals,clinics, health camps, blood donation camps, pharmacies, surgical equipment and pharmaceutical companies. 4 As per WHO fact sheet, hospital wastes comprise of non-hazardous waste (85%), hazardous infectious waste (10%) and hazardous non-infectious waste (5%). In short, approximately 10-20% of the waste generated by the above mentioned units is reported to be infectious or hazardous.…”
Section: Introductionmentioning
confidence: 99%